2016
DOI: 10.15253/2175-6783.2016000400007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sensory perception of sweet taste in people with Diabetes Mellitus type 2

Abstract: Objective: to evaluate the perception of patients with type 2 diabetes through the threshold index test for the sweet taste. Methods: a cross-sectional study with 80 adults of both genders, divided into two groups: control, composed of non-diabetics, and test, with diabetic patients. The evaluation of sensory perception held by the sensitivity test to determine the threshold index. The tests were conducted on five sections containing different concentrations of sucrose. Statistical analysis was held using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Some researchers observed that the average thresholds to detect sweet taste were higher for diabetic patients compared to non-diabetes showing a decreased or loss of sensitivity in diabetics [24]. This loss of sensitivity might contribute to increase in sugar consumption among diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers observed that the average thresholds to detect sweet taste were higher for diabetic patients compared to non-diabetes showing a decreased or loss of sensitivity in diabetics [24]. This loss of sensitivity might contribute to increase in sugar consumption among diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…19 The loss of taste sensitivity of children with ASD for sweet taste is highlighted when compared to the loss of taste sensitivity related to chronic diseases or inappropriate habits. In a study with adults with type 2 diabetes mellitus, the mean threshold index value for sucrose sweetness was 2.48 g / l. 18 In another study conducted with alcoholics under treatment, a mean threshold index value of 3.78 g / L sucrose 19 was found, and results in users of antidepressant drugs with a threshold index of 3.86 g / L sucrose. 20 It may contribute, by decreasing and / or losing sensitivity to sweet taste, to increase the intake of processed carbohydrates, influencing the secretion of insulin, responsible for sugar homeostasis.…”
Section: Resultsmentioning
confidence: 98%
“…Diabetic individuals, alcoholics, and users of antidepressant medications were excluded, as impairment in taste sensitivity is evident in these groups. [18][19][20] A structured questionnaire was applied to the families of children with ASD and to families of children without diagnosis of ASD who participated in the research to characterize the group, and this questionnaire collected information such as age, gender and skin color.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, taste perception occurs in taste buds, the primary sensory cells responsible for taste, and that are able to recognize basic tastes such as sweet, sour, salty, bitter and umami (10) .…”
Section: Introductionmentioning
confidence: 99%